Comparative study of the inhibitory effects of different antibiotic administration routes on bone healing in a rat tibial infection model - Han, Xiaoyu; Wang, Wei; Shen, Zengli; Lv, Lisong; Lin, Bingyuan; Ren, Haiyong; Liu, Yiyang; Guo, Qiaofeng; Kai, Huang; Wang, Xiang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of intravenous versus oral antibiotic treatments in managing bone infections, particularly osteomyelitis, using a rat tibial infection model.MethodsA tibial bone infection model was established in twelve-week-old Wistar rats via injection of Staphylococcus aureus at a cortical defect site. After six weeks, rats were treated with vancomycin (intravenous), cefazolin (intravenous), ciprofloxacin (oral), or ciprofloxacin combined with rifampin (oral). Microbial analysis, blood analysis for pro-inflammatory cytokines, micro-computed tomography (μCT), histological analysis, and osteoclast activity were used to assess the efficacy of each treatment.ResultsBlood analysis showed significant reductions in white blood cell count and pro-inflammatory cytokines in the intravenous treatment groups, especially with vancomycin. μCT imaging revealed better preservation of bone structure in intravenous treatment groups, while oral treatments resulted in more pronounced structural deterioration. Microbial analysis confirmed a lower bacterial load in the intravenous groups, particularly vancomycin, compared to oral treatments. Histological analysis revealed reduced inflammation, lower fibrosis, and minimal bacterial presence in intravenous groups. Osteoclast activity was notably reduced in the vancomycin and cefazolin groups, indicating better control of bone resorption.ConclusionIntravenous administration of vancomycin demonstrated superior efficacy in controlling bone infection, reducing inflammation, and preserving bone structure compared to oral treatments. While ciprofloxacin and the ciprofloxacin-rifampin combination showed some efficacy, they were less effective than intravenous vancomycin, likely due to lower bioavailability and insufficient drug penetration in bone tissue.